Political economics and possibilism : towards an open notion of development (2017)
Hirschman was both a pioneer and a dissenter of development economics. He shares with the high theory the virtues and misfortunes of committing to modernize the underdeveloped world, but his exposure to the politics of development in Latin America gave new life to his early insights. Revealing the political dimensions of his concepts on economic development, Hirschman provides some mini-building blocks for a political economics consistent with an open notion of development. This inquiry, however, should not be seen exclusively through a methodological lens; it is grounded on his possibilism, a claim about modernity and the possibility of change. This article reconsiders the legacy of Hirschman's thought for current debates on development and calls for recuperating his commitment to open societies.